Flexural Capacity of Concrete Beams Strengthened Using GFRP Sheet after Seawater Immersion. (2015) - Sultan, Mufti Amir; Djamaluddin, Rudy; Tjaronge, Wihardi; Parung, Herman
Abstract: Structures built in the marine environment need to be carefully designed, due to the possibility of chloride ion penetration into the concrete. Among these attempts, FRP was evaluated as one of the best methods to deal with the problem because FRP does not corrode even in marine environment. This study presents the results of the application of GFRP sheet for strengthening of the concrete beams. A series of specimen of reinforced concrete beams with dimension 15×20×330 cm were cast. The samples were tested under different duration of the immersion of sea water. Beams were immersed in sea water for 1 month (BF1 ), 3 months (BF3 ) and 6 months (BF6 ). Three specimens were prepared control beam without immersion to sea water (BF0 ). The results indicated that the flexural capacity of BF1, BF3, and BF6 when compared to that of BF0 decreased by 2.65%, 2.73% and 3.78% respectively. The decreasing was caused by the weakening of the bonding capacity GFRP due to the influence of sea water immersion.